A Land Productivity Of The Intercropping Shallot (Allium Ascalonicum L) And Chili Pepper (Capsicum Frutescens L) With Liquid Organic Fertilizer And Solid Organic Fertilizer - Selvia - Sutriana; Saripah Ulpah; Raisa Baharuddin (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Shallot and cayenne pepper are two national superior commodities that must continue to be cultivated in order to meet the daily needs of the community. The purpose of the study was to determine the land productivity of the shallot and cayenne pepper intercropping system with POC Biological and Solid treatment. This research was carried out at the Experimental Farm of the Faculty of Agriculture, Islamic University of Riau for 6 months, starting from October 2020 to March 2021. The study used a completely randomized design with 2 factorials, the first was the dose of Solid fertilizer with 4 treatment levels, namely 0 tons/ha, 5 tons /ha, 10 tons/ha, 15 tons/ha and the second is the concentration of Biological POC with 5 treatment levels, namely 0 ml/l water, 2 ml/l water, 4 ml/l water, 6 ml/l water, 8 ml/ l water. Parameters observed in shallot plants were plant height, number of tubers per clump, wet bulb weight per plant, dry bulb weight per plant, and in cayenne pepper plants were plant height, number of fruits per plant and fruit weight per plant. Observational data were analyzed statistically and continued with the further BNJ test at the 5% level. The results showed that the Solid and POC hayati treatment in shallots had a significant effect, with the best treatment being 4 ml/l water and 10 tons/ha. Meanwhile, the cayenne pepper plant has no effect except for plant height.